1990
DOI: 10.1159/000163583
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Melanocyte-Stimulating Hormone Immunoreactivity in Melanoma Cells

Abstract: Using a radioimmunoassay specific for α-melanocyte-stimulating hormone (α-MSH), significant levels of immunoreactivity were detected in a range of murine and human melanoma cell lines, including a series of ras-transfected melanocytes. The levels found in the melanoma cell lines tested varied, and overall were higher than in non-melanoma cell lines assayed for comparison. Furthermore the highest levels of immunoreactivity measured tended to be in the least differentiated and most metastatic melanoma lines. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 17 publications
3
39
0
Order By: Relevance
“…Previous research has shown that aMSH (and aMSH analogues) can suppress melanoma cell proliferation (Legros et al, 1981;Jiang et al, 1995;Smalley and Eisen, 2000), but our results demonstrate an aMSH-induced reduction in proliferation in the wild type MC1R transfected cell lines, whereas this decrease in cell numbers was not observed in the variant MC1R transfected melanoma cells. It has been reported that melanoma cells synthesize and release aMSH in vitro and in vivo (Ghanem et al, 1989;Lunec et al, 1990;Loir et al, 1998). It is therefore possible that the inability of aMSH to inhibit proliferation in melanoma cells from individuals with MC1R variants could increase the likelihood of the melanoma cells becoming established at an early stage in the epidermis and subsequently in the dermis, thereby rendering these people more susceptible to melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that aMSH (and aMSH analogues) can suppress melanoma cell proliferation (Legros et al, 1981;Jiang et al, 1995;Smalley and Eisen, 2000), but our results demonstrate an aMSH-induced reduction in proliferation in the wild type MC1R transfected cell lines, whereas this decrease in cell numbers was not observed in the variant MC1R transfected melanoma cells. It has been reported that melanoma cells synthesize and release aMSH in vitro and in vivo (Ghanem et al, 1989;Lunec et al, 1990;Loir et al, 1998). It is therefore possible that the inability of aMSH to inhibit proliferation in melanoma cells from individuals with MC1R variants could increase the likelihood of the melanoma cells becoming established at an early stage in the epidermis and subsequently in the dermis, thereby rendering these people more susceptible to melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers have interpreted the results of these studies as suggesting the MC1R variants alter skin cancer development and/or progression through mechanisms which are independent of their effects on pigmentation. In the case of cutaneous melanoma, it has previously been shown that the tumour cells can synthesize and release alpha-melanocyte stimulating hormone (aMSH), the ligand for the MC1 receptor (Ghanem et al, 1989;Lunec et al, 1990;Loir et al, 1998). Because MC1R is expressed by melanoma cells, it is likely that the aMSH released by the tumour cells has autocrine activity on the melanoma cells, as well as effects on other cell types, including monocytes/ macrophages and lymphocytes, which also express melanocortin receptors (Luger et al, 2000;AbdelMalek, 2001;Neumann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While the addition of aMSH to neonatal mouse mela nocyte cultures [57] and NDP-MSH to Cloudman mela noma cells [58] induce dendricity, Herlyn et al [59] found that a-MSH induced a certain degree of clustering of neo natal human melanocytes without affecting dendricity. However, Hunt et al [24,27] POMC gene expression has been demonstrated in mu rine and hamster melanoma cells [67] and an immunoreactive a-MSH-like peptide has been identified in human and murine melanoma cells [68], This raises the possibili ty that, in melanoma cells at least, POMC peptides may have an autocrine function in stimulating proliferation. POMC peptides have also been shown to affect experi mental metastasis of murine melanoma cells [15].…”
Section: The Effect Of Msh On Melanocyte Morphologymentioning
confidence: 99%
“…α-MSH is a proopiomelanocortin-derived peptide which is produced mainly in pituitary gland. However it has been reported that the peptide is produced in keratinocytes and melanocytes [5, 6]. In this study, we revealed the increase of α-MSH expression in melanocytes treated with Metharmon-F™.…”
Section: Discussionmentioning
confidence: 44%